(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Klebsiella pneumoniae is bacteria gram-negative opportunistic pathogen that causes a variety of infectious diseases. Aim of the study: The present study aimed to isolate K. pneumoniae, and finding out the extent of the spread of the blaOXA -1 and blaOXA -48 genes responsible for antibiotics resistance. Materials and methods: the detection of Klebsiella pneumoniae on morphological and biochemical tests and then assured with VITEK-2 system, and genotyping of blaOXA-1 and blaOXA-48 genes in isolates was done by PCR technique. Results: One hundred and fifty-eight samples were collected randomly from adults who suffers from respiratory tract infection, urinary tract infection, Inflamed burns and wounds including both sexes from different hospitals in Baghdad especially Teaching Laboratories of Medical City, Al-Mahmodia health centre, Al-Yarmouk hospital,and Al-Mahmodia hospital during the period from September to November 2020.Shown the results by VITEK-2 system for all isolates that 50 (31.6%) isolate from the total of isolates were K. pneumonia .Molecular test was detected via Polymerase Chain Reaction (PCR) conventional proved to be effective for the detection of diffuse blaOXA -1 gene at 66.7% and the present results demonstrated a high significant presence at P≤0.0001 among isolates. While the prevalence of 5 isolates of the blaOXA -48 gene was 16.6% showed significant difference between the isolate types with p value ≤ 0.01. Conclusions: K. pneumoniae was the most bacterial species isolated from patient with pneumonia and our results indicate the spread of the OXA genes.